EAU Guidelines on Non-Muscle-invasive Urothelial Carcinoma of the Bladder: Update 2016 - Babjuk, Marko; Böhle, Andreas; Burger, Maximilian; Capoun, Otakar; Cohen, Daniel; Compérat, Eva M; Hernández, Virginia; Kaasinen, Eero; Palou, Joan; Rouprêt, Morgan; van Rhijn, Bas W G; Shariat, Shahrokh F; et al. (European urology, 2017)
CONTEXT: The European Association of Urology (EAU) panel on Non-muscle-invasive Bladder Cancer (NMIBC) released an updated version of the guidelines on Non-muscle-invasive Bladder Cancer. OBJECTIVE: To present the 2016 EAU guidelines on NMIBC. EVIDENCE ACQUISITION: A broad and comprehensive scoping exercise covering all areas of the NMIBC guidelines published between April 1, 2014, and May 31, 2015, was performed. Databases covered by the search included Medline, Embase, and the Cochrane Libraries. Previous guidelines were updated, and levels of evidence and grades of recommendation were assigned. EVIDENCE SYNTHESIS: Tumours staged as TaT1 or carcinoma in situ (CIS) are grouped as NMIBC. Diagnosis depends on cystoscopy and histologic evaluation of the tissue obtained by transurethral resection of the bladder (TURB) in papillary tumours or by multiple bladder biopsies in CIS. In papillary lesions, a complete TURB is essential for the patient's prognosis. If the initial resection is incomplete, there is no muscle in the specimen, or a high-grade or T1 tumour is detected, a second TURB should be performed within 2-6 wk. The risks of both recurrence and progression may be estimated for individual patients using the European Organisation for Research and Treatment of Cancer (EORTC) scoring system and risk tables. The stratification of patients into low-, intermediate-, and high-risk groups is pivotal to recommending adjuvant treatment. For patients with a low-risk tumour and intermediate-risk patients at a lower risk of recurrence, one immediate instillation of chemotherapy is recommended. Patients with an intermediate-risk tumour should receive 1 yr of full-dose bacillus Calmette-Guérin (BCG) intravesical immunotherapy or instillations of chemotherapy for a maximum of 1 yr. In patients with high-risk tumours, full-dose intravesical BCG for 1-3 yr is indicated. In patients at highest risk of tumour progression, immediate radical cystectomy (RC) should be considered. RC is recommended in BCG-refractory tumours. The long version of the guidelines is available at the EAU Web site (www.uroweb.org/guidelines). CONCLUSIONS: These abridged EAU guidelines present updated information on the diagnosis and treatment of NMIBC for incorporation into clinical practice. PATIENT SUMMARY: The European Association of Urology has released updated guidelines on Non-muscle-invasive Bladder Cancer (NMIBC). Stratification of patients into low-, intermediate-, and high-risk groups is essential for decisions about adjuvant intravesical instillations. Risk tables can be used to estimate risks of recurrence and progression. Radical cystectomy should be considered only in case of failure of instillations or in NMIBC with the highest risk of progression.
Keywords: Neoplasm Staging; cystektomie; Bladder cancer; karcinom z přechodných buněk; Intravesical chemotherapy; Europe; invazivní růst nádoru; Urothelial carcinoma; Adjuvants, Immunologic; lidé; aplikace intravezikální; Evropa; Antineoplastic Agents; staging nádorů; protinádorové látky; Transurethral resection (TUR); urologie; Diagnosis; společnosti lékařské; Carcinoma in Situ; Bacillus Calmette-Guérin (BCG); Societies, Medical; cystoskopie; Urology; směrnice pro lékařskou praxi jako téma; Urinary Bladder Neoplasms; Urinary Bladder; Administration, Intravesical; nádory močového měchýře; močový měchýř; Carcinoma, Transitional Cell; Practice Guidelines as Topic; Prognosis; Guidelines; BCG vakcína; BCG Vaccine; Cystectomy; hladké svalstvo; Neoplasm Invasiveness; adjuvancia imunologická; European Association of Urology; Cystoscopy; Muscle, Smooth; karcinom in situ; Humans